Chapter 1 Introduction The entanglements of comics and migration - Vuorinne, Anna (Taylor & Francis, 2023)
This chapter introduces the broad theoretical approach of the volume while connecting it to previous research on comics and migration. The chapter demonstrates that while a crucial aspect of comics in relation to migration is that the former represents the latter, there are several other practices, uses, and functions alongside representation that connect these two. The chapter suggests that when analysing the intersections of comics and migration, comics ought to be regarded in relation to a wide range of practices and considered in their respective cultural, social, and political contexts. Most of the chapter is devoted to mapping the current state of research on the entanglements of comics and migration and presenting the chapters of the volume. It foregrounds the following perspectives: cartooning and stereotypes, graphic life writing and identity, memory and trauma, witnessing and human rights, readerly engagements and empathy, advocacy and NGO-produced comics, comics workshops and self-expression, and comics in education. The modest proposal of the introductory chapter is that comics studies should move towards paying more attention to the multiple entanglements that comics in general - and comics and migration in particular - are involved in.